Implementasi Pembelajaran Berdiferensiasi Menggunakan Model Discovery Learning Pada Mata Pelajaran Instalasi Motor Listrik - Syafitri, Tazkia Rama; Asnil, Asnil (Jurnal Pendidikan Teknik Elektro, 2024)
Student learning outcomes are still low which is caused by students' lack of activeness in lesson activities, lack of preparation before lessons begin, and students' lack of concentration in learning which only lasts for a short period when presenting lesson material. Research is needed to improve student learning outcomes in the Electric Motor Installation subject at SMK Negeri 1 Mandau with differentiated learning using the discovery learning model. This research uses experimental research with the Pre-Experiment type with a One-Group Pretest Posttest design. The research subjects were students of class XI TITL 2 SMK Negeri 1 Mandau, even semester of the 2023/2024 academic year, consisting of 33 students. This study's research instrument was multiple choice consisting of 40 questions. The results of the pretest and post-test were analyzed using the N-Gain Score and completeness of learning outcomes. The results of the research show that the application of differentiated learning using the discovery learning model in the Electric Motor Installation subject class XI TITL 2 at SMK Negeri 1 Mandau can improve student learning outcomes. These results can be seen from the results of the pretest and posttest which were analyzed using the N-Gain Score formula which fell into the medium category and the results of the analysis of the completeness of learning outcomes showed that many students reached the KKM set by the school.